The Management of Traumatic Optic Neuropathy: A Systematic Review and Meta-Analysis - Mohammad Fallahzadeh; Amirreza Veisi; Faezeh Tajari; Zahra Khorrami; Mehri Farhang Ranjbar; Roozbeh Tavanaei; Navid Ghassembaglou; Seyed Hadi Aghili (Archives of Academic Emergency Medicine)
Introduction: Traumatic optic neuropathy (TON) is a serious condition resulting from optic nerve injury, often due to head trauma. This study systematically reviews the existing literature to evaluate the effectiveness of various treatments in improving visual outcomes in TON patients.